Upaya Pengurus Pondok Pesantren Dalam Meningkatkan Karakter Kedisiplinan Santri Di Pondok Pesantren Modern Minhajul Muttaqin - Ahamad N; Ayu Lestari (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang OKU Timur Sumatera Selatan, 2025)
The background to this research, changing times and demands for quality education or good quality education, is something that must be faced by every educational institution. Therefore, educational institutions must be able to analyze or know the strengths, weaknesses, opportunities and challenges that the educational institution will face and then make strategic plans to improve the quality of education. So the aims of this research are: (1) to find out how to implement SWOT analysis in improving the quality of education at SMP Negeri 2 Mesuji Makmur, (2) to find out what the supporting and inhibiting factors are for SWOT analysis, (3) to find out what the advantages and disadvantages are. from SMP Negeri 2 Mesuji Makmur. This research was conducted using qualitative research methods with the aim of describing or illustrating the phenomena that exist at the research location. The subject of this research is the Principal of SMP Negeri 2 Mesuji Makmur through data collection using observation, interview and documentation methods, so that the research results are structured systematically, the research steps in analyzing the data are first, by selecting the main things in and focusing on them. The important thing is, secondly, presenting data in the form of brief descriptions, tables and the like, thirdly drawing conclusions to answer the problem formulation from the start.